Contribution of Interest in Learning and Learning Environment to Learning Outcomes of Training Participants at the Job Training Center (BLK) Padang City - Abdul Rahim; Irmawita Irmawita (Universitas Negeri Padang, 2021)
Learning outcomes are the acquisition of learning carried out during the training and their competence tested at the end of the training period. Training with interests will get more results than no individual interests. The learning environment becomes important during the teaching and learning process for participants who take part in the training at the Job Training Center. This research was conducted with the aim of knowing the Contribution of Learning Interest and Learning Environment to the Learning Outcomes of Training Participants at the Job Training Center (BLK) Padang City. The type of research used is quantitative research while the method is associative. The population is BLK Padang training participants for the period 1 of 2021 in 18 vocational schools totaling 288 participants with a sample of 74 people. Data collection techniques in the form of questionnaires with data collection tools in the form of questionnaires and documentation. The data analysis technique is percentage, then continued with categorization through the respondent's achievement level formula and hypothesis testing using the t-test formula. The results of the analysis of interest in learning obtained the value of tcount > ttable, namely 8,613 > 1,987 with a significant result of 0.000 < 0.05, this illustrates that there is a significant influence between interest in learning and learning outcomes. Then the learning environment is obtained from the value of tcount > ttable, namely -6.384 < 1.987 with a significant result of 0.000 < 0.05, this illustrates that there is a significant influence between the learning environment on learning outcomes. By using a one-way test so that the results are Ho is accepted and Ha is rejected. This proves simultaneously (together) interest in learning and the learning environment has a significant influence on learning outcomes.